(untitled) (Scientific journal of the Fergana State University, 2026)
This article examines what information technologies are used in physics laboratory workshops and how they affect learning. They emphasize its importance in communicating new knowledge to students, in developing students’ intelligence, in shaping their perception and formulating conclusions.